Ecophysiological response of Astronium fraxinifolium (Anacardiaceae) in degraded and non-degraded brazilian Cerrado - Leite, Marilaine Cristina Marques [UNESP]; Araujo, Maycon Anderson [UNESP]; Souza, Lucas Anjos; Martins, Aline Redondo [UNESP]; Camargos, Liliane Santos [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2021)
Plants native from Cerrado generally have peculiar characteristics that allow tolerating water and nutritional stress. Astronium fraxinifolium is a Anacardiaceae tree of from Brazilian Cerrado. The aim of this research was to characterize A. fraxinifolium leaves morphophysiologically, in order to recognize characteristics related to acclimatization of the species in different soil conditions. Two populations of A. fraxinifolium were sampled in different study areas, A1 (Degraded Soil) and A2 (“Undegraded Soil”). Nitrogen compounds, total carbohydrates, chlorophyll, nutritional content, stomatal density and gas exchanges were quantified, comparing the areas. A high number of stomata was observed on the abaxial surface of A. fraxinifolium leaves, with a higher density occurring in A1 individuals. The values ​​of chlorophyll and boron content were significantly higher in A2 plants. It’s possible that the lowest concentration of boron in A1 plants is related to chlorophyll production. Regardinf the other analysis, there weren’t significant differences between the areas. The results show that this species undergoes changes in production of chlorophyll, but liquid photosynthesis isn’t impaired, considering the low chlorophyll content in A1 being compensated by the higher stomatal density. Thus, these changes may be the result of acclimating this species to different environmental conditions to which it’s exposed.

Plantas nativas do Cerrado geralmente apresentam características peculiares que permitem tolerar o estresse hídrico e nutricional. Astronium fraxinifolium, é uma das espécies arbóreas de Anacardiaceae do Cerrado brasileiro. O objetivo desta pesquisa foi caracterizar morfofisiologicamente as folhas de A. fraxinifolium, com o objetivo de reconhecer características relacionadas a aclimatação da espécie em diferentes condições de solo. Para tanto, duas populações de A. fraxinifolium foram amostradas em diferentes áreas de estudo, A1 (Solo degradado) e A2 (“Solo não degradado”). A partir dessas amostras foram quantificados compostos nitrogenados, carboidratos totais, amido, clorofila, conteúdo nutricional, densidade estomática, trocas gasosas, alocação de carbono e altura da parte aérea, comparando as áreas de estudo. Um número elevado de estômatos foi observado na superfície abaxial das folhas de A. fraxinifolium, com uma densidade estomática mais elevada ocorrendo em indivíduos de A1. Já os valores de clorofila a, b e total foram significativamente maiores em A2. O conteúdo nutricional não diferiu entre as áreas, exceto o boro, que apresenta maior concentração nas plantas de A2. É possível que a menor concentração de boro nas plantas A1 esteja relacionado a produção de clorofila. Em relação às demais análises, não houve diferenças significativas entre as áreas. Os resultados mostram que esta espécie sofre alterações na produção de clorofila, mas a fotossíntese líquida não é perturbada, sendo o baixo teor de clorofila em A1 compensado pela maior densidade estomática. Assim, essas mudanças podem ser o resultado da aclimatação dessa espécie às diferentes condições ambientais às quais está exposta.
Keywords: chlorophyll content; nutritional deficiency; physiological characterization; stomatal density; teor de clorofila; deficiência nutricional; caracterização fisiológica; densidade estomática